A Reliable Data Collection Protocol Based on Erasure-Resilient Code in Asymmetric Wireless Sensor Networks - Jian-Jun Lei; Taehyun Park; Gu-In Kwon (International Journal of Distributed Sensor Networks)
This paper presents RECPE, a reliable collection protocol for aggregating data packets from all the sensor nodes to the sink in a large-scale WSN (wireless sensor network). Unlike some well-known reliable data collection protocols such as CTP (Collection Tree Protocol) that uses ETX (expected transmission count) as the routing metric, RECPE exploits ETF (expected transmission count over forward links) to construct a one-way collection tree, which avoids missing some good routes and reduces the effect of asymmetric link in the network. Crucially, RECPE guarantees the reliability by erasure-resilient codes in the application layer without retransmission required by other reliable protocols. Therefore, some lower layers such as data link layer only need to conduct best-effort data delivery. Meanwhile, to improve efficiency, RECPE also exploits Trickle algorithm to reduce routing beacons and pipeline data delivery to prevent self-interference. We evaluate the performance of RECPE via TOSSIM simulations, and our results show that, in comparison with CTP (the de facto data collection protocol for TinyOS), RECPE can obtain significant performance in terms of delivery cost, latency, and packet loss rate for reliable data collection especially in asymmetric link networks.